Drug disposition and pharmacokinetics : principles and applications for medicine, toxicology and biotechnology - Curry, Stephen H.; Whelpton, Robin (Wiley, 2022)
"An authoritative, comprehensive book on the fate of drug molecules in the body, including implications for pharmacological and clinical effects. The text provides a unique, balanced approach, examining the specific physical and biological factors affecting the absorption, distribution, metabolism and excretion of drugs, together with mathematical assessment of the concentrations in plasma and body fluids. Understanding the equations requires little more than a basic knowledge of algebra, laws of indices and logarithms, and very simple calculus"--